2015
DOI: 10.1017/s1755020314000379
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatizing Semantic Theories of Truth?

Abstract: We discuss the interplay between the axiomatic and the semantic approach to truth. Often, semantic constructions have guided the development of axiomatic theories and certain axiomatic theories have been claimed to capture a semantic construction. We ask under which conditions an axiomatic theory captures a semantic construction. After discussing some potential criteria, we focus on the criterion of N-categoricity and discuss its usefulness and limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…This was proved for the Strong Kleene scheme by Burgess [3] and Cantini [5] (the result was already announced by Kripke), for the van Fraassen scheme by Burgess [3], for the Cantini scheme by Cantini [6], 1 and for Leitgeb's [21] theory (which is based on his notion of semantic dependence) by Welch [40]. The proof in [40] was generalized by Fischer et al [8] to cover a range of further supervaluational schemes (for example, supervaluations based on maximal consistent extensions). Leitgeb's theory is not defined in the Kripkean way, but in Beringer and Schindler [1] it is shown that Leitgeb's theory coincides with the least fixed point of a particular 3-valued valuation scheme that we dubbed the Leitgeb valuation scheme, V L .…”
Section: Thus Whenever (N E A) Is a Fixed Point M E Coincides Witmentioning
confidence: 81%
See 1 more Smart Citation
“…This was proved for the Strong Kleene scheme by Burgess [3] and Cantini [5] (the result was already announced by Kripke), for the van Fraassen scheme by Burgess [3], for the Cantini scheme by Cantini [6], 1 and for Leitgeb's [21] theory (which is based on his notion of semantic dependence) by Welch [40]. The proof in [40] was generalized by Fischer et al [8] to cover a range of further supervaluational schemes (for example, supervaluations based on maximal consistent extensions). Leitgeb's theory is not defined in the Kripkean way, but in Beringer and Schindler [1] it is shown that Leitgeb's theory coincides with the least fixed point of a particular 3-valued valuation scheme that we dubbed the Leitgeb valuation scheme, V L .…”
Section: Thus Whenever (N E A) Is a Fixed Point M E Coincides Witmentioning
confidence: 81%
“…There are some further philosophical issues on which our results may shed some light, such as the question of what constitues a good axiomatization of a semantic truth theory (Fischer et al [8]), or the question of the 'unsubstantiality' of truth (Horsten [17], Shapiro [31], Ketland [19], Halbach [13]). However, I won't attempt to draw any substantial philosophical conclusions in this paper and leave a proper assessment for another occasion.…”
Section: Introductionmentioning
confidence: 99%
“…8 Since we work with a two-sided sequent calculus with a special treatment of negation, the usual initial sequents will come in two versions.…”
Section: Pkf: Adding Compositional Truth Sequents To Palmentioning
confidence: 99%
“…In Fischer et al [8] a criterion of adequacy for axiomatic theories trying to capture a semantic theory was discussed. There it was already mentioned that PKF is adequate with respect to the class of strong Kleene fixed-points based on the standard interpretation of arithmetic.…”
Section: Lemma 12mentioning
confidence: 99%
“…The second of these results shows we have developed what Fischer et al (2015) call an N-categorical axiomatisation, although they would not consider the ω-rule as a permissible axiom as they only consider recursively enumerable theories. Theorem 5.13 could also be taken to show that KFC ∪ InteractionAx, which is a recursively enumerable theory, is an N-categorical axiomatisation given the structure M.…”
mentioning
confidence: 99%